Determinants of artificial intelligence adoption in the audit profession in Saudi Arabia - Alaskar, Mohammad (2023)
Artificial intelligence is considered as the fourth industrial revolution and is having a profound impact on our lives. Amid the recent rapid development of artificial intelligence, the framework of determinants of the use of artificial intelligence in the business environment such as the audit profession is still far from the rapid development of artificial intelligence. This thesis provides a framework for the determinants that influence the decision of using artificial intelligence. It expands and modifies the Unified Theory of Technology Acceptance and Use to cover important aspects that auditors should consider when using artificial intelligence. The new framework of artificial intelligence acceptance was empirically tested via a questionnaire sent to 403 auditors working in Saudi Arabia. Moreover, to verify and obtain a profound understanding of the result of the questionnaire, it was followed by an interview with 26 external auditors. Based on the questionnaire and interview, this thesis finds that ethical factor is considered by external auditors as one of the most important determinants of artificial intelligence technology adoption. The findings also indicate that auditors consider both facilitating conditions, performance expectancy, and effort expectancy when intending to implement artificial intelligence in audit engagements. Indeed, auditors consider facilitating conditions as the most influential factor when adopting artificial intelligence technology. This thesis contributes in framing the determinants of artificial intelligence acceptance and empirically tested these determinants. Also, it contributes to the existing literature by exploring the determinants influencing the acceptance of advanced technology within the audit profession in Middle East countries. Moreover, the thesis contributes to the societal debate on artificial intelligence and ethics by providing empirical evidence of ethical concerns by the potential users of artificial intelligence technology. The thesis contributes to identifying six dimensions of ethical concerns regarding the acceptance of artificial intelligence in the audit profession. These dimensions are as follows: substitution of human labour, confidentiality and data protection, independence, auditability of audit processes, repurposing client data, and professional scepticism and judgment.